Cross-country analysis of alternative five factor personality trait profiles. (1st June 2019) - Kövi, Zsuzsanna; Aluja, Anton; Glicksohn, Joseph; Blanch, Angel; Morizot, Julien; Wang, Wei; Barry, Oumar; Hansenne, Michel; Carvalho, André; Valdivia, Mauricio; Desrichard, Olivier; Hyphantis, Thomas; et al.
Abstract: The aim of our study was to examine the typical personality profiles of the Alternative Five Factor Model with its new factor-facet version questionnaire (Zuckerman-Kuhlman-Aluja Personality Questionnaire, 2010) on a large, cross-country database. The total sample of this study included 15, 529 participants from 23 sub-samples from 22 countries and with 16 different languages. The sample consisted of university students and staff members. We applied model-based clustering both separately on each sample and on the total sample. Agreement between country-specific and total sample clustering was similar for the three-, four- and five-cluster solutions with Cohen's kappa coefficients ranging from 0.59 to 0.60. The optimal cluster number based on BIC values increased with sample size, but the most common one was five with the following typical profiles: overcontrolled, resilient, undercontrolled, reserved, and ordinary. Highlights: This study examined the typical personality profiles on a cross-country database. The optimal cluster number was five. Overcontrolled, resilient, undercontrolled, reserved, and ordinary types emerged. The five types showed moderate cross-country invariance. Ordinary profile may reflect a response style.